Prototype of Lighting Intensity Administration in Work Room With Sound Control and Fuzzy Logic Control - Syafitri, Nesi; Ibnu Faderi, Raja; Suryani, Des; Labellapansa, Ause (UIR PRESS, 2022)
The use of indoor and outdoor lighting systems that are still passive makes the use of electrical energy less efficient and classified as wasteful. From the problems that occur in the system that is running, the researchers need to develop a more dynamic system by utilizing the Tsukamoto FLC method and Arduino using voice control to adjust the intensity of the light in the room. After implementing as well as testing the system that has been made, namely the Prototype of Light Intensity Regulator in the Work Room With Voice Control and Fuzzy Logic Control using NodeMCU ESP8266, it is concluded that each component can function according to its function which can be controlled and monitored from the application, implements fuzzy logic control on nodemcu with time and activity input variables obtained from the android application while the room light intensity variable is obtained from the light sensor or LDR. The results of the fuzzy process will adjust the light which is controlled by nodemcu. With the fuzzy logic control in this system, it can adjust the light to the room conditions, making it much more efficient.